Running performance after adaptation to acutely intermittent hypoxia - Wood, M. R.; Dowson, M. N.; Hopkins, W. G. (European Journal of Sport Science, 2006)
To quantify the effects of adaptation to acutely intermittent hypoxia on running performance, we randomized 29 trained male hockey and soccer players in double-blind fashion to altitude or placebo groups for 15 days of daily use of a functional or placebo hypoxic re-breathing device. Each day's exposure consisted of alternately breathing stale and fresh air for 6 and 4 min respectively over 1 h. Oxygen saturation was monitored with pulse oximeters and progressively reduced in the hypoxia group (90% on Day 1, 77% on Day 15; equivalent to altitudes of 3600-6000 m above sea level). Performance tests were an incremental run to maximum speed followed by six maximal-effort running sprints; tests were performed 1 day before, 3 days after, and 12 days after the 15-day treatment. Relative to placebo, at 3 days post treatment the hypoxia group showed a mean increase in maximum speed of 2.0% (90% confidence limits, ±0.5%); sprint speed was relatively faster by 1.5% (±1.7%) in the first sprint through 7.0% (±1.5%) in the last; there were also substantial reductions in exercise lactate concentration and resting and exercise heart rate. Substantial effects on performance were still present 9 days later. Thus, adaptation to acutely intermittent hypoxia substantially improves high-intensity running performance.